E- Waste Management: An Emerging Challenge in Nepal - Khatri, Bishnu B. (NUTA Journal, 2019)
E-waste is one of the fastest growing waste streams, globally and volume of E-waste has been increasing day by day in developing countries, like Nepal. The aim of this paper is to assess the situation of E-waste in Nepal and its growing concerns of management. The study has utilized secondary information generated by published and unpublished documents. The paper revealed that socio-economic development and technological advancement are the main drivers of increasing trend of E-waste. The increasing trend of e-waste generation and lack legal provision in Nepal has come up as one of the major environmental problems and challenges for its proper management. Considering its adverse potential eco-toxicological impacts, the legal instrument of E-waste management is urgently needed addressing e-waste handling, storage, transportation, recycling, and final disposal.